Weighted Product dalam Sistem Rekomendasi Pemilihan Karyawan Berbasis Web - Muazir, Novia Hasdyna, Rahmat (LPPM-UNIKI, 2021)
An employee selection recommendation system is needed in selecting the best employees. This study uses the Weighted Product method in the recommendation system. The data used is employee data at the Sejahtera Swalayan Lhokseumawe. Based on the analysis carried out, the results of this study show that the ranking of the best employees is Nasir in the first place with a vector V value of 0.081657618, Alfian in second place with a V vector value of 0.077227007 and Muhibuddin in third place with a V vector value of 0.07372706. The system is built based on the web using the PHP programming language.